Infection by a Giant Virus (AaV) Induces Widespread Physiological Reprogramming in Aureococcus anophagefferens CCMP1984 – A Harmful Bloom Algae - Moniruzzaman, Mohammad; Gann, Eric R.; Wilhelm, Steven W. (Frontiers in Microbiology, 2018)
While viruses with distinct phylogenetic origins and different nucleic acid types can infect and lyse eukaryotic phytoplankton, “giant” dsDNA viruses have been found to be associated with important ecological processes, including the collapse of algal blooms. However, the molecular aspects of giant virus – host interactions remain largely unknown. Aureococcus anophagefferens virus (AaV), a giant virus in the Mimiviridae clade, is known to play a critical role in regulating the fate of brown tide blooms caused by the pelagophyte Aureococcus anophagefferens. To understand the physiological response of A. anophagefferens CCMP1984 upon AaV infection, we studied the transcriptomic landscape of this host-virus pair over an entire infection cycle using a RNA-sequencing approach. A massive transcriptional response of the host was evident as early as 5 min post-infection, with modulation of specific processes likely related to both host defense mechanism(s) and viral takeover of the cell. Infected Aureococcus showed a relative suppression of host-cell transcripts associated with photosynthesis, cytoskeleton formation, fatty acid and carbohydrate biosynthesis. In contrast, host cell processes related to protein synthesis, polyamine biosynthesis, cellular respiration, transcription and RNA processing were overrepresented compared to the healthy cultures at different stages of the infection cycle. A large number of redox active host-selenoproteins were overexpressed, which suggested that viral replication and assembly progresses in a highly oxidative environment. The majority (99.2%) of annotated AaV genes were expressed at some point during the infection cycle and demonstrated a clear temporal-expression pattern and an increasing relative expression for the majority of the genes through the time course. We detected a putative early promoter motif for AaV, which was highly similar to the early promoter elements of two other Mimiviridae members, indicating some degree of evolutionary conservation of gene regulation within this clade. This large-scale transcriptome study provides insights into the Aureococcus cells infected by a giant virus, and establishes a foundation to test hypotheses regarding metabolic and regulatory processes critical for AaV and other Mimiviridae members.